2014
DOI: 10.1051/0004-6361/201424755
|View full text |Cite
|
Sign up to set email alerts
|

Inclination dependence of Lyman-αproperties in a turbulent disk galaxy

Abstract: We present simulations of Lyman-α radiation transfer in an isolated disk galaxy with a turbulence subgrid model, multiphase interstellar medium and detailed star formation modeling. We investigate the influence of inclination on the observed Lyα properties for different snapshots. The Lyα spectrum, equivalent width distribution, and escape fractions vary significantly with the detailed morphology of the disk, leading to variations from one snapshot to another. In particular, we find that supernova-driven cavit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 33 publications
1
58
0
Order By: Relevance
“…Its Lyα photometric properties characterize Mrk 1486 as one of the highest Lyα luminosites (L Lyα = 1.11 × 10 42 erg s −1 ), Lyα equivalent widths (EW(Lyα) = 45 Å), and Lyα escape fractions of the LARS sample (fesc(Lyα) = 0.174; Hayes et al 2014). While these properties indicate a very easy escape of Lyα photons from the galaxy, this result clearly contradicts recent numerical simulations that suggest the formation of either a very attenuated Lyα emission line or a pronounced Lyα absorption feature in the spectra of highly inclined low-mass disk galaxies (Laursen & Sommer-Larsen 2007;Laursen et al 2009;Verhamme et al 2012;Behrens & Braun 2014). Based on the calculation of Lyα and UV continuum radiative transfer inside the ISM of high-resolution, dusty, isolated disk simulations, all numerical works have clearly highlighted a strong inclination effect on the Lyα properties of disk galaxies.…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…Its Lyα photometric properties characterize Mrk 1486 as one of the highest Lyα luminosites (L Lyα = 1.11 × 10 42 erg s −1 ), Lyα equivalent widths (EW(Lyα) = 45 Å), and Lyα escape fractions of the LARS sample (fesc(Lyα) = 0.174; Hayes et al 2014). While these properties indicate a very easy escape of Lyα photons from the galaxy, this result clearly contradicts recent numerical simulations that suggest the formation of either a very attenuated Lyα emission line or a pronounced Lyα absorption feature in the spectra of highly inclined low-mass disk galaxies (Laursen & Sommer-Larsen 2007;Laursen et al 2009;Verhamme et al 2012;Behrens & Braun 2014). Based on the calculation of Lyα and UV continuum radiative transfer inside the ISM of high-resolution, dusty, isolated disk simulations, all numerical works have clearly highlighted a strong inclination effect on the Lyα properties of disk galaxies.…”
Section: Introductionmentioning
confidence: 70%
“…Without calling into question the accuracy of the work of Verhamme et al (2012) and Behrens & Braun (2014), the discrepancy observed between the Lyα properties of Mrk 1486 and the simulated galaxies seems to originate in a small difference in the galactic wind properties of these objects. Although the simulated galaxies of Verhamme et al (2012) and Behrens & Braun (2014) exhibit very extended tenuous and ionized outflowing materials from the disk, the galactic winds of Mrk 1486 differ from the simulated ones in that they entrain a higher mass of neutral gas (HI) at large distances from the galaxy disk.…”
Section: Hi and Dust Clumpiness Inside The Disk And The Outflowing Halosmentioning
confidence: 86%
See 3 more Smart Citations